2009
DOI: 10.48550/arxiv.0905.1698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The hyperfine transition of 3He+ as a probe of the intergalactic medium

J. S. Bagla,
Abraham Loeb

Abstract: We explore the prospects of using the hyperfine transition of 3 He II as a probe of the intergalactic medium. The emission signal from ionized regions during reionization is expected to be anti-correlated with 21 cm maps. The predicted emission signal from Ly-α blobs at lower redshifts is detectable with future radio observatories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Intensity mapping was originally developed for 21 cm radiation (Hogan & Rees 1979;Scott & Rees 1990;Madau et al 1997), but has been studied for several other lines (in increasing frequency): deuterium (Sigurdson & Furlanetto 2006), 3 He+ (McQuinn & Switzer 2009;Bagla & Loeb 2009), CO (Righi et al 2008;Carilli 2011;Lidz et al 2011;Breysse et al 2014;Li et al 2015), C II (Gong et al 2012;Silva et al 2014;Uzgil et al 2014;Yue et al 2015), Lyα ance amount to different forms of dimensionality reduction. Liu & Tegmark (2011) show that most of the covariance that distinguishes foregrounds is in the ν, ν ′ directions rather than combinations involving angular separations.…”
Section: Introductionmentioning
confidence: 99%
“…Intensity mapping was originally developed for 21 cm radiation (Hogan & Rees 1979;Scott & Rees 1990;Madau et al 1997), but has been studied for several other lines (in increasing frequency): deuterium (Sigurdson & Furlanetto 2006), 3 He+ (McQuinn & Switzer 2009;Bagla & Loeb 2009), CO (Righi et al 2008;Carilli 2011;Lidz et al 2011;Breysse et al 2014;Li et al 2015), C II (Gong et al 2012;Silva et al 2014;Uzgil et al 2014;Yue et al 2015), Lyα ance amount to different forms of dimensionality reduction. Liu & Tegmark (2011) show that most of the covariance that distinguishes foregrounds is in the ν, ν ′ directions rather than combinations involving angular separations.…”
Section: Introductionmentioning
confidence: 99%
“…The spin temperature of 3 He + is determined by the collisional process and HeII Lyα radiative transfer via the HeII analog of the Wouthuysen-Field effect (Bagla & Loeb 2009;McQuinn & Switzer 2009;Takeuchi et al 2014):…”
Section: Data Availabilitymentioning
confidence: 99%
“…Among these, the LOw Frequency ARray 1 (LOFAR), the Murchison Widefield Array 2 (MWA), the Hydrogen Epoch of Reionization Array 3 (HERA), the Precision Array for Probing the Epoch of Reionization 4 (PAPER) and the upcoming Square Kilometer Array 5 (SKA). While efforts to probe the high-z IGM have focused extensively on the 21 cm line, the hyperfine transition of 3 He + at 8.66 GHz (3.5 cm) also offers a unique insight into some astrophysical phenomena prevalent in the early universe (Furlanetto et al 2006;Bagla & Loeb 2009;McQuinn & Switzer 2009;Takeuchi et al 2014;Vasiliev et al 2019). In addition to being a probe of the high-z evolution of the helium component of gas, Bagla & Loeb (2009) suggested that this feature could also in principle be used to obtain independent constraints on the 21 cm signal, because the evolution of both HII and HeII are driven by stellar type sources during the epoch of (hydrogen) reionization, and thus the 21 cm and 3.5 cm signals are expected to be anti-correlated at these redshifts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sigurdson & Furlanetto (2006) have suggested a challenging possibility of determination of D/H abundance ratio by looking at hyperfine structure line at high redshift of both the H and D. Signals from IGMs and dense objects at high redshifts through the 3 He hyperfine transition has been studied. Detailed physics and suggested observational plans were presented (McQuinn & Switzer 2009), and the anticorrelation of H i 21 cm maps and 3 He ii 3 cm maps was suggested (Bagla & Loeb 2009).…”
Section: Introductionmentioning
confidence: 99%